THE RELATIONSHIP BETWEEN KNOWLEDGE LEVEL AND ATTITUDE OF THIRD TRIMESTER PREGNANT WOMEN WITH MATERNAL DELIVERY PREPARATION AT ANDALAS PADANG HEALTH CENTER IN 2020 - Satria, Epi; Aninora, Novia Rita (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2021)
About 90% of maternal deaths occur during childbirth, 95% of which are the cause of death after childbirth. using an analytical design with a cross-sectional study approach, which was carried out on July 23 to August 1, 2021. The population in this study were 37. Data was collected by interview using a questionnaire. And data analysis using univariate and bivariate analysis with chi-square test. The results of this study found that 59.5% of pregnant women already had preparation for childbirth. As many as 70.3% of pregnant women in the third trimester have a low level of knowledge about preparation for childbirth. And 40.5% of third trimester pregnant women have a negative attitude about preparation for childbirth. It can be concluded from the results of the chi-square statistical test, it was found that there was a significant relationship between the level of knowledge and maternal labor preparation with a p value of 0.026 and there was a significant relationship between the attitudes of pregnant women in the third trimester and maternal labor preparation with a p value of 0.020. It is hoped that from the results of this study, health workers will always provide counseling so that pregnant women will still gain knowledge about their pregnancy, especially in preparation for childbirth.